Pattuppui Ri Ade’e, Pasanre’i Ri Syara’E: Character Education Based On Religious Values and Local Wisdom - Hadi Pajarianto (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The Locus of this research is The people of South Sulawesi who are upholding their highest value which are Siri’ focus on shame and self-esteem as human. This cultural value becomes the strength  binding the caracther of the nation, based on the  cultural and religious values which often lost to western culture. The Western culture has positive values such as hard working, tolerance, discipline, and as well as negative values which based from permisifm. The subjects of this study were 60 PAUD education teachers using quantitative survey methods with questionnaires as instruments. The research findings show (1) the relationship of religious values with the nationalism attitude of PAUD teachers by 0.948; (2) the relationship between religious values and the integrity of PAUD teachers is 0.747; (3) the relationship between religious values and the PAUD teacher's cooperation attitude of 0.761; (4) the relationship between the understanding of local wisdom with the nationalism attitude of PAUD teachers by 0.422; (5) the relationship between understanding local wisdom and PAUD teacher integrity is 0.378; and (6) there is a significant and positive relationship between the understanding of local wisdom with the PAUD teacher's cooperation attitude of 0.412. In Indonesian society, The religious values which related with integrity and cooperative such as ta’awun, syura’ and hubbul wathan. On the other hand, the religious values such as adele’, rebba’ sipatokkong, and Mali siparappe’. These values become the binder in various life aspects, including education